VERBAL INTERACTION BETWEEN TEACHER AND STUDENTS IN ENGLISH CLASSROOM IN SMP SWASTA PAHLAWAN NASIONAL MEDAN - Oktaviani Tampubolon; Zainuddin Zainuddin; Meisuri Meisuri (Universitas Negeri Medan, 2018)
This study deals with verbal interaction between teacher and students at SMP Swasta Pahlawan Nasional. The objectives of this study were to find out the category of verbal interaction between the teacher and the students in the classroom, and the dominant category of verbal interaction in the classroom between teacher and students. Data of the research was taken from 28 students of eight grades which took an English class involved one English teacher who taught in the class. The data in this research collected by using interview and videotaping. The result of the study showed that both the teachers and the students were aware and understood that interaction was important in English learning. They also understood that to be able to interact well, they needed to practice. But, the understanding was not supported by what they did in classroom. The teacher did not give much interactive activity in class. It seemed that the teachers did not believe in the students' competence. The students were not active in practicing their English by asking questions or expressing their idea or opinion, and the most dominant interaction between teacher and students were direct teacher interaction. Keywords : verbal interaction, teacher and students